Social Studies Teachers' Efforts in Implementing Character Education: A Descriptive Analysis Study - Desika Handayani; Ririn Rizki Apdasuli (Southeast Asian Journal of Global Trends and Issues in Education, 2025)
This study investigates the efforts of social studies teachers in implementing character education at SMP Negeri 15 Kota Bengkulu, emphasizing how moral and civic values are integrated into classroom learning to shape students’ character. Using a qualitative descriptive approach, data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using Miles and Huberman’s Interactive Model, which includes data reduction, data display, and conclusion drawing. The findings reveal that social studies teachers view character education as essential in fostering students’ moral awareness and civic responsibility, focusing on five core values: honesty, responsibility, social care, tolerance, and nationalism. These values are integrated into lessons through discussions, collaborative learning, and real-life contextual examples. The implementation of character education has led to positive behavioral changes among students and a more meaningful learning atmosphere. The study concludes that consistent teacher modeling, collaborative school culture, and supportive educational policies are crucial for sustaining effective character education, with implications for strengthening teacher competence and promoting holistic student development.